2011 IEEE Custom Integrated Circuits Conference (CICC) 2011
DOI: 10.1109/cicc.2011.6055336
|View full text |Cite
|
Sign up to set email alerts
|

An integrated four-phase buck converter delivering 1A/mm<sup>2</sup> with 700ps controller delay and network-on-chip load in 45-nm SOI

Abstract: Abstract-We present a four-phase integrated buck converter in 45nm SOI technology. The controller uses unlatched pulse-width modulation (PWM) with nonlinear gain to provide both stable small-signal dynamics and fast response (~700ps) to large input and output transients. This fast control approach reduces the required output capacitance by 5X in comparison to a controller with latched PWM at similar operating point. The converter switches at 80MHz and delivers 1A/mm 2 at 83% efficiency and 0.66 conversion rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Higher switching frequencies allow lower inductor values. Recent work has demonstrated that switching frequencies in excess of 100 MHz can be used in cutting-edge CMOS processes while still achieving efficiencies approaching 90% [10][11][12][13]. However, to achieve efficiencies greater than 90%, switching frequencies are still limited to ~100MHz as shown in Fig.…”
Section: Problem and Opportunitymentioning
confidence: 99%
“…Higher switching frequencies allow lower inductor values. Recent work has demonstrated that switching frequencies in excess of 100 MHz can be used in cutting-edge CMOS processes while still achieving efficiencies approaching 90% [10][11][12][13]. However, to achieve efficiencies greater than 90%, switching frequencies are still limited to ~100MHz as shown in Fig.…”
Section: Problem and Opportunitymentioning
confidence: 99%
“…Planar spiral or other inductor topologies that can be constructed using the interconnects of a typical CMOS process are too resistive to provide efficient on-chip power conversion at reasonable current densities [16]. The efficient use of surface mount technology (SMT) air-core inductors, which can provide a current density up to A/mm [17], has been successfully demonstrated [9]- [13]. However, the size and discrete nature of these devices hinders the scalability of any IVR incorporating discrete SMT inductors.…”
Section: Introductionmentioning
confidence: 99%
“…This work presents an early prototype switched-inductor IVR using 2.5D chip stacking for inductor integration. , while the bridge output voltage for each phase, V BRIDGE , drives another RC filter to generate the inner feedback voltage, V FB,I [3]. The pole in both RC low-pass filters is chosen to be below f s so that the steady state amplitude of V REF, I and V FB,I is around 150mV, which gives a small signal feedback gain of ~30V/V and ensures stable loop dynamics.…”
mentioning
confidence: 99%
“…In the event of a large load current transient, the error in the output voltage, V OUT , will couple across C FB onto V FB,I and the comparator will react immediately to reduce overshoot in V OUT . This fast non-linear response can reduce the required decoupling capacitance on the output voltage [3]. Also residing on the IC is a 64-tile network-on-chip (NoC) consisting of four parallel, heterogeneous, physical network planes with independent frequency domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation